Authorial interpretation of the abstract photographic image: between intuitive perception and compositional analysis - Hordiichuk, Tetiana (Педагогічна Академія: наукові записки, 2026)
The relevance of the study is determined by the growing role of abstract photography in contemporary artistic practice and the increasing interest in the mechanisms through which artistic meaning is constructed within a visually dominated culture. In the contemporary artistic environment, the abstract photographic image increasingly functions not as a means of representing objective reality but as an autonomous system of visual relationships in which meaning emerges through the interaction of form, perception, and authorial interpretation. This actualizes the need for a deeper investigation of the relationship between intuitive perception and compositional analysis as key factors in the interpretation of abstract photographic imagery. The purpose of the article is to investigate the mechanisms of authorial interpretation in abstract photography through the interaction of intuitive perception and compositional analysis, as well as to substantiate their significance in the formation of artistic meaning within contemporary photographic practice. Methods. The study employed methods of theoretical generalization, analysis and synthesis of scientific sources, structural-compositional analysis, visual interpretation, a comparative-analytical approach, and the method of conceptual generalization. Results. The conceptual foundations of authorial interpretation in abstract photography were investigated, and the principal aesthetic factors influencing the perception of the photographic image were identified. The interaction between intuitive perception and compositional organization in the creation and interpretation of abstract photographic works was analyzed. The significance of visual elements, formal structures, and compositional strategies in the construction of artistic meaning was revealed. It was established that the expressive potential of the abstract photographic image is formed not through the representation of recognizable objects but through a system of visual relationships capable of activating associative, emotional, and conceptual mechanisms of perception. The principal theoretical and practical challenges of interpreting abstract photography were identified, including the absence of unified evaluation criteria, the growing influence of digital technologies on visual reading processes, and the complexity of reconciling subjective and analytical models of interpretation.Conclusions. It was proven that the most productive approach to the interpretation of abstract photographic imagery is based on the integration of intuitive visual experience and systematic compositional analysis. Prospects for further research are associated with the investigation of cognitive mechanisms involved in the perception of abstract photographic images, the empirical analysis of contemporary interpretative practices, and the examination of the impact of digital and AI-oriented technologies on the formation of artistic meaning in abstract photography.